Teen Internet Dependency. A Research Conducted among Young People in Rome - Zbigniew Formella; Marco Nicoli (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Both existent and newly arising social problems induce a continuous search for new approaches, forms and methods of social work. The most recent  examples of concepts utilizing the ideas of empowerment include, among others, a solution oriented approach, the model of supported employment or an approach based on the creation and development of communities. Moreover, one must draw attention to motivating dialogue and family group conferences as well as video training communication as well as the outreach method. Bearing in mind the necessity of engaging in work with individuals who need the assistance of a social worker, the goal of considerations was to show selected innovative solutions in contemporary social work.